Design a voltage regulator for a power supply - Lim, Wen Ying (2016)
Voltage regulators are widely used in electronics as it is used to maintain a constant output voltage and regulate the unregulated input voltage from the power supply. There are 2 commonly used voltage regulators namely linear regulator and switching regulators. Both types of voltage regulators are explored and design.A simple linear regulator consist of Zener diode as voltage reference and transistors as regulating devices. Regulating devices are place parallel with the load (shunt regulators) or between input source and the load (series regulator). Both regulators are design to explore the different configurations. Switching regulators uses active element which switches on and off to maintain an average value of output voltage and inductors as storage element. There are 3 common type of DC-DC converters, namely buck, boost and buck boost. Control system is an important part of switching regulators as it is use to adjust pulse width to keep output voltage constant and provide good transient response. Buck converter with voltage mode control is design to explore switching regulators. Linear and switching regulators are design and built on MULTSIM and PSIM to simulate before building on breadboard to test the practical aspects. MATLAB is use as a mathematical software tool to calculate the components needed and plotting bode plot for control system transient response. This project also aims to compare the efficiencies of both linear and switching regulators.